2019
DOI: 10.1002/cctc.201900590
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Mixed‐Ligand Complexes in Cu−CHA by Reaction of Cu Nitrates with NO/NH3 at Low Temperature

Abstract: The reactivity with a NO/NH3 mixture of Cu‐nitrate complexes formed on the surface of a Cu−CHA catalyst active in the Selective Catalytic Reduction of NOx with NH3 (NH3−SCR) was followed at 50 °C by in situ spectroscopic techniques. The catalyst (Si/Al=15; Cu/Al=0.5) was first exposed to NO/O2 (mimicking the SCR oxidative half‐cycle), mainly resulting in the formation of chelating bidentate framework‐interacting CuII‐nitrates. These intermediates were gradually detached from the framework in the presence of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 61 publications
(132 reference statements)
7
42
0
Order By: Relevance
“…The aqueous copper nitrate reference is labelled as Cu II (NO x ) y due to the negligible difference between the XANES spectra of Cu II (NO 3 ) 2 and Cu II (NO 2 ) x (H 2 O) 6‐x . Cu I (NH 3 ) 2 and Cu II (NH 3 ) 4 are thought to be related directly to solvated linear Cu I[13] and square planar Cu II[41] and may not be limited to ligands composing solely of NH 3 . In the recent work of Negri et al the square planar Cu II species was demonstrated to be composed of mixed ligands .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aqueous copper nitrate reference is labelled as Cu II (NO x ) y due to the negligible difference between the XANES spectra of Cu II (NO 3 ) 2 and Cu II (NO 2 ) x (H 2 O) 6‐x . Cu I (NH 3 ) 2 and Cu II (NH 3 ) 4 are thought to be related directly to solvated linear Cu I[13] and square planar Cu II[41] and may not be limited to ligands composing solely of NH 3 . In the recent work of Negri et al the square planar Cu II species was demonstrated to be composed of mixed ligands .…”
Section: Resultsmentioning
confidence: 99%
“…[8,40] Cu I (NH 3 ) 2 and Cu II (NH 3 ) 4 are thought to be related directly to solvated linear Cu I [13] and square planar Cu II [41] and may not be limited to ligands composing solely of NH 3 . [19,42] In the recent work of Negri et al the square planar Cu II species was demonstrated to be composed of mixed ligands. [42] Herein these species will be described as solvated linear Cu I and square planar Cu II species, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2+ (NH 3 ) 3 (NO 3 )). 4,45,46 It is clear, however, that the identication of intermediate states as achieved here can be very useful in guiding the design of the next generation of new and related technologies for deNO x applications, perhaps using cationic components that could be more active or at least more environmentally benign or at risk than copper.…”
Section: Figmentioning
confidence: 98%
“…The aim is to define structure‐reactivity correlations for a rational design of materials, often with the support of modeling and in collaboration with industry. Important fields of study are partial oxidation reactions, including the selective catalytic reduction of NO x (SCR) and the direct methane to methanol conversion …”
mentioning
confidence: 99%